The Influence of Entrepreneurship Orientation, Product Innovation and Competitive Advantage on Marketing Performance of Hat SMEs in Sidoarjo Regency - Ayu Silviana Santoso; Mudji Astuti (Indonesian Journal of Cultural and Community Development, 2022)
This study aims to determine the effect of entrepreneurial orientation, product innovation and competitive advantage both partially and simultaneously on the marketing performance of Hat SMEs in Punggul Village, Gedangan District, Sidoarjo Regency. This research method uses a quantitative approach. Data collection is done by using a questionnaire. The population in this study were all owners of Hat SMEs in Punggul Village, Gedangan District, Sidoarjo Regency with 85 people. The sample used is 85 respondents. The sampling technique used was saturated sampling technique and the analytical technique used by the researcher was multiple linear regression analysis using the SPSS version 24 program. The results showed that partially entrepreneurial orientation, product innovation and competitive advantage had an effect on marketing performance. Meanwhile, simultaneously entrepreneurial orientation, product innovation and competitive advantage affect marketing performance.